Moves and language expressions of conclusion section of thesis at postgraduate English education study program of Bengkulu University - Andana, Fitra; Azwandi , Azwandi (Yayasan Mitra Persada Nusantara, 2024)
The conclusion section is a compulsory chapter of a thesis and a dissertation. A good thesis or dissertation conclusion should tell the reader what work has been done and why the issue is being taken. The conclusion section of theses in the field of English language education is a form of a summary statement of the cases investigated. The summary is expressed with certain language expressions, indicating each of the 5-move of the section. The purpose of this research was to describe moves and language expressions of conclusion sections of theses written by the postgraduate English Language Study Program students of Bengkulu University. The study employed the descriptive quantitative method. The subjects of the research were 40 theses of postgraduate students of Bengkulu University which were selected purposively. The data of the conclusion moves were examined based on the five-move model proposed by Bunton (2005), and the language features were analysed based on Morley (2014). The results show that move 3 (Practical application/implications/recommendations embedded elsewhere) and move 4 (recommendations for future research embedded elsewhere) were used by 33 authors (88%) and 35 authors (77.5%) respectively. However, the move formats of the conclusion section were widely varied, nonconforming to Bunton’s model. The language expressions used in the majority of the conclusion sections have adhered to guidelines proposed by Morley (2014), but many authors tended to choose weaker language expressions to emphasize the points. This study concludes that five Move Models of the conclusion section proposed by Bunton (2014) have not been reflected markedly in most of the thesis conclusion sections written by the Postgraduate English Language Study Program students of Bengkulu University, although some moves have been written in suitable language expressions.